Modelling Low Reynolds Number Vortex-Induced Vibration Problems with a Fixed Mesh Fluid-Solid Interaction Formulation - Cruchaga-Ssa., M; Gonzalez-Cornejo, F (American Institute of Physics, 2017)
The present work reports a fluid-rigid solid interaction formulation described within the framework of a fixed-mesh technique. The numerical analysis is focussed on the study of a vortex-induced vibration (VIV) of a circular cylinder at low Reynolds number. The proposed numerical scheme encompasses the fluid dynamics computation in an Eulerian domain where the body is embedded using a collection of markers to describe its shape, and the rigid solid s motion is obtained with the well-known Newton s law. The body s velocity is imposed on the fluid domain through a penalty technique on the embedded fluid-solid interface. The fluid tractions acting on the solid are computed from the fluid dynamic solution of the flow around the body. The resulting forces are considered to solve the solid motion. The numerical code is validated by contrasting the obtained results with those reported in the literature using different approaches for simulating the flow past a fixed circular cylinder as a benchmark problem. Moreover, a mesh convergence analysis is also done providing a satisfactory response. In particular, a VIV problem is analyzed, emphasizing the description of the synchronization phenomenon.